More than beliefs: Subject areas and teachers' integration of laptops in secondary teaching. (27th January 2014) - Howard, Sarah K.; Chan, Amy; Caputi, Peter
Abstract: The purpose of this paper is to explore the relationship of subject areas to teachers' technology integration. Educational technology research has often identified "culture clashes" to explain differences in technology use between subject areas. These clashes are frequently attributed to core features, values and beliefs held in the subject area cultures, but there has been little research analyzing the relationship between subject areas and integration. Using a validated path model as a conceptual framework, this paper presents an analysis of the relationship between three subject areas (English, Mathematics, Science) and known factors of teacher beliefs and readiness to use technology in teaching, which directly impact on secondary‐level teachers' technology integration, over three years. Findings show that time and subject areas are both associated with teachers' readiness, but only subject areas are associated with teachers' beliefs. Implications for practice and future research are discussed.